War comics : a postcolonial perspective - Viljoen, Jeanne-Marie (New York : Routledge, 2020)
"This book focuses on non-fictional, visual narratives (including comics; graphic narratives; animated documentaries and online, interactive documentaries) that attempt to represent violent experiences, primarily in the Levant"--
Introduction: towards a postcolonial understanding of violence -- Graphic narratives, bringing the ineffable into the frame -- 'Dark' writing the Khan Younis massacre -- 'Dark' writing the Sabra and Shatila massacre -- 'Dark' writing violent experiences in new aesthetic forms -- Summary -- Why this book matters.
OCLC-licensed vendor bibliographic record.
Keywords: Documentary comic books, strips, etc -- History and criticism; Documentary films -- History and criticism; Animated films -- History and critcism; War in literature; Violence in literature; Psychic trauma in literature; Arab-Israeli conflict -- Literature and the conflict